DISPATCHING RULES FOR SCHEDULING PRODUCT PORTFOLIOS - Shiau, Jiun-Yan; Lin, Jui-Chuan; Jiang, Pei-Rou (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
During the production and marketing coordination stage, scheduling product portfolios allows for evaluating the utility performance of production lines and assists in determining the priorities of product portfolios that need to be assigned. Feasible or optimal scheduling of work orders for product portfolios is subject to a sequence of combinations of work orders. Thus, it involves many scheduling models. It is beyond the scope of a single scheduling model to address this issue. Many mathematical scheduling models and hybrid dispatching rules are too complex to be included in a packaged ERP solution, and they may not even be necessary at the enterprise-wide decision-making level. Therefore, we developed a static scheduling program for job shop problems and conducted experiments in which we tested the ten most common dispatching rules in various scenarios. According to the testing results, seven dispatching rules are suitable for most scenarios and recommended for ERP system implementation.